Optimization of ultrasonication time on the production of ZnO-SiO2 nanocomposite as photocatalytic material - Qomariyah, Lailatul; Faizah, Nurul; Karisma, Achmad Dwitama; Putra, Nicky Rahmana; Rabbani, Sulthan; Kalloka, Sultan Hendra Mahardi (Center of Biomass & Renewable Energy (CBIORE), 2025)
Nanocomposite ZnO-SiO2 is widely known for its efficacy as a semiconductor photocatalyst. Current nanocomposite production methods face challenges like particle agglomeration and inconsistent particle size control. To overcome this problem, the ultrasonication method was used to prevent agglomeration and produce composites in nanoscale, where this study synthesized ZnO-SiO2 for photocatalytic degradation of dye color. To prepare this nanocomposite, the ultrasonication time was varied from 0 to 45 minutes to understand the particle properties and the effectivity on the photocatalytic activity. Silica was prepared from water glass via sol-gel method to produce colloidal SiO2 nanoparticles and then mixed with ZnO with the ratio of 3% wt and subjected to ultrasonication method. Under various ultrasonication time, the FTIR analysis shows the Si-O peak at 895 cm-1 indicates the presence of SiO2 particles. The XRD validate the formation of ZnO-SiO2 nanoparticles, supporting the FTIR analysis. The best nanoparticle properties were achieved with 45 minutes of ultrasonication. The SEM analysis confirms the present of SiO2 and ZnO. From BET analysis, ZnO-SiO2 has a high surface area (117.64 m2/g), moderate pore volume (0.46 cm3/g), and small particle pore size (11.59 nm). The photocatalytic activity of ZnO-SiO₂ nanocomposites was evaluated by the degradation of methylene blue (MB) under sunlight and the best performance reached by the nanocomposite prepared under 45 minutes ultrasonication. The results show that the ultrasonication technique efficiently reduces agglomeration, as indicated by a reduction in particle diameter from 35.04 nm (pure ZnO) to 11.59 nm (ZnO-SiO₂), and significantly enhances photocatalytic activity, achieving 97% degradation of MB under sunlight after 180 minutes. The aforementioned technique demonstrates significant potential for industrial use, providing higher efficiency and expandability in manufacturing superior photocatalytic substances.